Assessment of Delirium In Critically Ill Patients: Utilizing The Confusion Assessment Method for The Intensive Care Unit (CAM-ICU) - Tantawy, Nayera Mohamed; Abd-Elaziz, Wafaa Wahdan (Journal of Medical Biomedical and Applied Sciences, 2018)
Delirium is a widespread neurological confusion detected in intensive care units (ICU). Patients in ICU are at veryhigh risk for the development of delirium due to numerous elements. Routine examining of all patients in the ICU forthe presence of delirium is extremely important to its successful management. Nurses are at the forefront to identify,control, and even prevent ICU delirium. The main aim of the study was to assess the delirium in ICU patients. Thestudy involved 52 patients were recruited from 80 consecutive admissions to the General ICU, Mansoura InternationalHospital during a period of 6 months (February to July 2017). Patient assessment sheet was used for data collectionincluding Demographic characteristic and health relevant data, The Richmond Agitation-Sedation Scale (RASS), fordelirium recognition in acute care setting, the confusion estimation method can be utilized as it is a legitimized toolwith excessive level of sensitivity and specificity. The results of the study revealed that the delirium detected in largestpercentage (65.3%) of patients, and there were numerous threat factors for delirium were recognized together with, longduration of ICU stay, respiratory diseases, heart diseases, renal diseases, infection, and hypertension. The findings ofthe study highlighted the need for more interest ought to be paid to the implementation of a tested delirium screeninginstrument which includes the Confusion Assessment Method for the ICU ( CAM-ICU ) and should be a part of habitualevery day vital care.